Best practices for the management of patients with non-tuberculous mycobacterial pulmonary disease according to a german nationwide analysis of expert centers - Rohde, Gernot Gerhard Ulrich; Eichinger, Monika; Gläser, Sven; Heiß-Neumann, Marion; Kehrmann, Jan; Neurohr, Claus; Obradovic, Marko; Kröger-Kilian, Tim; Loebel, Tobias; Taube, Christian (Healthcare, 2023)
Non-tuberculous mycobacterial pulmonary disease (NTM-PD) is a chronic inflammatory lung disease caused by infection with non-tuberculous mycobacteria (NTM). International guidelines provide evidence-based recommendations on appropriate diagnosis and treatment strategies, but there is a need for sharing day-to-day best practice between treatment centers to optimize patient care. This is particularly valuable for rare diseases like NTM-PD. In this cross-sectional analysis of NTM-PD management in Germany, medical and administrative staff from seven treatment centers were interviewed to identify best practice in the diagnosis, treatment, and ongoing management of patients with NTM-PD, including related hospital infrastructure and administration processes. A prioritization led to a collection of best practices for the management of patients with NTM-PD in Germany, which is presented here. Selected current best practices included performance of regular sputum tests for diagnosis, use of medical reports, and regular follow-up visits as well as increased interaction between physicians across different specialties. Future best practices that may be implemented to overcome current barriers comprised disease awareness activities, patient empowerment, and new approaches to enhance physician interaction. Challenges related to their implementation are also discussed and will help to raise disease awareness. The presented best practices may guide and optimize patient management in other centers.
Veröffentlicht: 22. September 2023
Gesehen am 10.01.2024